2020
DOI: 10.1136/bmjgh-2019-002161
|View full text |Cite
|
Sign up to set email alerts
|

Policy dialogue as a collaborative tool for multistakeholder health governance: a scoping study

Abstract: IntroductionHealth system governance is the cornerstone of performant, equitable and sustainable health systems aiming towards universal health coverage. Global health actors have increasingly been using policy dialogue (PD) as a governance tool to engage with both state and non-state stakeholders. Despite attempts to frame PD practices, it remains a catch-all term for both health systems professionals and researchers.MethodWe conducted a scoping study on PD. We identified 25 articles published in English betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…The contextualization of policy options stated in the policy brief during the policy dialogue is an invaluable takeaway from the policy dialogue, as demonstrated in our study. Evidence has shown the usefulness of policy dialogues in promoting stakeholder involvement in translating evidence to policy [ 17 , 18 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contextualization of policy options stated in the policy brief during the policy dialogue is an invaluable takeaway from the policy dialogue, as demonstrated in our study. Evidence has shown the usefulness of policy dialogues in promoting stakeholder involvement in translating evidence to policy [ 17 , 18 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that the sustainability can be improved if all conceived actions are integrated into existing policies, programs or processes. In addition, political capital and commitment—and particular, sustained funding—were seen as key to achieving many of the follow-up actions indicated by the policy dialogs [ 24 ]. We suggest that further research of this aspect could result in important longer-term learnings about policy dialog planning, implementation and overall impact.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, however, that feedback from participants in the CHRODIS PLUS national policy dialogs indicated that their efficacy as a tool would have been enhanced had the joint action envisioned providing sustained financial support to the dialog process, as well as a framework for monitoring implementation of related action plans over the short-, mid- and long-term. Current literature also supports the importance of sufficient financial commitment for policy dialog processes [ 24 ].…”
Section: Introductionmentioning
confidence: 96%
“…Case studies have offered few details about how civil society has been involved, or its influence (Berman et al, 2015;Kasonde and Campbell, 2012;Ongolo-Zogo et al, 2018;El-Jardali et al, 2020). The main challenge is lack of capacity: the capacity of convenors to host and facilitate debate by a mix of stakeholders, and the capacity of stakeholders to bring their group perspectives to debate the relevant evidence (Robert et al, 2020).…”
Section: Starting With the Uncertainty Of A Social System: Knowledge Mobilisationmentioning
confidence: 99%